Research Methods in Healthcare Epidemiology and Antimicrobial Stewardship—Observational Studies. (20th June 2016) - Snyder, Graham M.; Young, Heather; Varman, Meera; Milstone, Aaron M.; Harris, Anthony D.; Munoz-Price, Silvia
Abstract : Observational studies compare outcomes among subjects with and without an exposure of interest, without intervention from study investigators. Observational studies can be designed as a prospective or retrospective cohort study or as a case-control study. In healthcare epidemiology, these observational studies often take advantage of existing healthcare databases, making them more cost-effective than clinical trials and allowing analyses of rare outcomes. This paper addresses the importance of selecting a well-defined study population, highlights key considerations for study design, and offers potential solutions including biostatistical tools that are applicable to observational study designs. Infect Control Hosp Epidemiol 2016;1–6